2016
DOI: 10.18097/pbmc20166206683
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of perioperative corneal abrasions: alterations in tear film proteome

Abstract: Perioperative corneal abrasion is an ophthalmic complication commonly found in patients underwent general anesthesia. In this study, correlations between development of corneal injury and proteomic changes in tear film during general anesthesia were examined using an animal (rabbit) model. Being started after 1-h anesthesia, the process of accumulation of pathological changes in the cornea unequivocally led clinically significant abrasions following 3-6 h of the narcosis. The corneal damage was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…To this end, the animals were exposed to general anesthesia for 0.5-6 h and their corneas were subjected to clinical and morphological examination immediately after the narcosis. The results of fluorescein test indicated anesthesia time-dependent accumulation of corneal epithelium injury in accordance with our previous findings [ 39 ]. Statistical analysis revealed that the incidence of the corneal damage rose with the duration of the narcotic sleep reaching 100% of animals after 5-6 h of the anesthesia ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…To this end, the animals were exposed to general anesthesia for 0.5-6 h and their corneas were subjected to clinical and morphological examination immediately after the narcosis. The results of fluorescein test indicated anesthesia time-dependent accumulation of corneal epithelium injury in accordance with our previous findings [ 39 ]. Statistical analysis revealed that the incidence of the corneal damage rose with the duration of the narcotic sleep reaching 100% of animals after 5-6 h of the anesthesia ( Figure 1(a) ).…”
Section: Resultssupporting
confidence: 91%
“…A rabbit model of anesthesia-induced DES developed in our previous studies [ 6 , 39 ] was selected for further trialing of the antioxidant therapy using SkQ1 eye drops. In order to characterize the basic parameters of the model, we determined the incidence of DES symptoms in rabbits depending on the duration of general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[25]. In other mitochondrial targeting compounds [10,14,31], we observed that pre-treatment with TPP-Niacin signi cantly enhanced the MMP and improved the mitochondrial ultrastructure in a phenotypic analysis by EM, compared to H 2 O 2 alone. Based on these data, we next analyzed gene expressions of mitochondria-related genes, such as OXPHOS subunits, mitochondrial dynamics, and mitochondrial DNA replication and transcription genes.…”
Section: Discussionmentioning
confidence: 85%